Combining Radiotherapy with Immunocheckpoint Inhibitors or CAR-T in Renal Cell Carcinoma - Santoni, Matteo; Heng, Daniel Y.C.; Aurilio, Gaetano; Iozzelli, Andrea; Servi, Lucilla; Fabiani, Andrea; Giannini, Massimo; Mazzucchelli, Roberta; Cimadamore, Alessia; Scarpelli, Marina; Zaghloul, Mohamed S.; Battelli, Nicola; et al. (Current Drug Targets, 2020)
Radiotherapy is considered a second life in Renal Cell Carcinoma (RCC) patients, mainly due to the introduction of immune checkpoint inhibitors, such as anti-Programmed-death (PD)-1, alone or in combination with anti-Cytotoxic T-Lymphocyte Antigen (CTLA)-4. Several trials are investigating the efficacy/safety of immune checkpoint inhibitors in sequential or combined strategies with radiotherapy. Chimeric Antigen Receptor (CAR)-T cells therapy as a promising approach in cancer patients has opened the way to novel possibilities of integrating therapies. The identification of biomarkers of tumor response to these combinations represents a challenge in RCC, together with the research for the best partner for immunotherapy in metastatic patients. In this review we illustrated preclinical/clinical data on the integration of radiotherapy with immunocheckpoint inhibitors or CART cells in RCC.
Keywords: renal cell carcinoma